Phase Transition of Huntingtin: Factors and Pathological Relevance - Yang, Junsheng; Yang, Xiaotong (Frontiers in Genetics, 2020)
Formation of intracellular mutant Huntingtin (mHtt) aggregates is a hallmark of Huntington’s disease (HD). The mechanisms underlying mHtt aggregation, however, are still not fully understood. A few recent studies indicated mHtt undergoes phase transition, bringing new clues to understand how mHtt aggregates assemble. Here in this mini review, we will summarize these findings with a focus on the factors that affect mHtt phase transition. We will also discuss the possible pathological roles of mHtt phase separation in HD.